2012
DOI: 10.1590/s0100-83582012000100017
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade e absorção radicular do sulfentrazone em clones de eucalipto

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a seletividade e a absorção do sulfentrazone em clones de eucalipto. O primeiro experimento foi instalado em casa de vegetação, em delineamento inteiramente casualizado, com quatro repetições, no esquema fatorial 2 x 4, sendo duas doses do sulfentrazone (400 e 600 g ha -1) e quatro clones de eucalipto, híbridos de Eucalyptus grandis x E. urophylla (FB1, FB2, FB3 e FB4). Foram realizadas avaliações visuais de intoxicação das plantas de eucalipto e, no final do estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Carbonari et al (2012) observed that the eucalyptus clone that absorbed higher quantities of sulfentrazone showed greater reductions of dry mass, in addition to more intense visual symptoms. DOI: dx.doi.org/10.18671/scifor.v44n109.01 Table 4.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Carbonari et al (2012) observed that the eucalyptus clone that absorbed higher quantities of sulfentrazone showed greater reductions of dry mass, in addition to more intense visual symptoms. DOI: dx.doi.org/10.18671/scifor.v44n109.01 Table 4.…”
Section: Resultsmentioning
confidence: 95%
“…The symptoms observed in the plants ranged from purplish coloration of the secondary veins to in some cases of the entire foliar tissue. Carbonari et al (2012), evaluating the phytotoxicity of two sulfentrazone doses in two eucalyptus clones, observed significant selectivity differences between the two clones, with the higher sulfentrazone dose posing the most critical condition for both clones. The same authors found that difference in sensitivity between the two studied clones was related to differential absorption of sulfentrazone from the soil by eucalyptus roots.…”
Section: Resultsmentioning
confidence: 98%
“…The experimental design used in each herbicide was a randomized block design, in a 5 x 2 factorial scheme, with four replications, considering as factors the five herbicide doses and the two forms of application FLORESTA, Curitiba, PR, v. 50, n. 1, p. 1031-1040, jan/mar 2020. Araujo Neto, A. C. et.al.…”
Section: Methodsmentioning
confidence: 99%
“…After spraying sulfentrazone (400 and 600 g ha -1 ) in four Eucalyptus urograndis clones (FB1, FB2, FB3, FB4), Carbonari et al (2012) noted that clone FB3 showed greater dry mass reduction when compared to the other clones, and this reduction can be directly associated with the high levels of phytotoxicity observed. The concentrations of sulfentrazone absorbed by the plants were proportional to the dry mass reductions, indicating that variations in the eucalypt clones may be related to the differentiated absorption of the sulfentrazone.…”
Section: Sulfentrazonementioning
confidence: 99%
“…The major symptoms observed after sulfentrazone drift in eucalypt are purple leaves, necrosis, leaves with deformations and loss of apical dominance (Carbonari et al, 2012). Those symptoms can start from the seventh day after spraying (Takahashi et al, 2009).…”
Section: Sulfentrazonementioning
confidence: 99%